Salvadora persica agro-ecological suitability for oil production in Argentine dryland salinity - Falasca, Silvia Liliana (2015)
One of the major causes of crop stress is soil or water salinity. Thus, selection of the best species for cultivation in semiarid and arid climates is fundamental.Salvadora persica is an evergreen perennial halophyte that can grow under extreme conditions, from very dry environments to highly saline soils.Based on international bibliography, the authors outlined an agro-ecological zoning model to determine the potential cultivation zones for S. persica in Argentina. This model may be applied to any part of the world, using the agro-ecological limits presented in this work. All the maps were developed by the implementation of a geographic information system (GIS) that can be updated by the further incorporation of complementary information, with the consequent improvement of the original database.The overlap of the agroclimatic suitability map on the drylands´ saline soils and the drylands´ alkaline soils maps, determined the agro-ecological zoning. Since some areas in the agro-ecological zoning can overlap with land that is already assigned for other uses, protected areas, current land use/cover of the different zones, and urban areas maps were incorporated into the GIS and subtracted by a mask. This resulted in the delimitation of ?potential cultivation zoning?, thus avoiding possible conflicts surrounding the use of land and making the agro-ecological zonation more efficient.There is a broad agro-ecological zone for cultivation of S. persica that extends from Northern Argentina to approximately 41° South latitude, under dry-subhumid to semiarid climates. Lands classified with different degrees of suitability in the potential cultivation zoning could be used for production of this species for energy purposes on lands that are either unsuitable for food production or currently assigned for other purposes.This paper represents pioneering work since there are no previous studies concerning the introduction of S. persica in Argentina.